2017
DOI: 10.1111/pirs.12202
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dependence and heterogeneity in the location processes of new high‐tech firms in Nanjing, China

Abstract: Drawing upon township-level data on high-tech firms of Nanjing, China, this paper adopts a spatial econometric approach to examining the existence of spatial dependence and heterogeneity in the location processes of high-tech firms. The results show that some locational determinants of neighbouring townships exert significant impacts on the attractiveness of a certain township for high-tech firms. Besides, the marginal effects of some locational determinants are found to vary across space. In general, these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
1
14
0
2
Order By: Relevance
“…In fact, the significant roles of development zones in promoting agglomeration of high-tech firms and industries has been confirmed in many empirical studies (Li & Zhu, 2017;Zhang, Huang, Sun, & Wang, 2013). In fact, the significant roles of development zones in promoting agglomeration of high-tech firms and industries has been confirmed in many empirical studies (Li & Zhu, 2017;Zhang, Huang, Sun, & Wang, 2013).…”
Section: Development Zones In China's Suburban Areasmentioning
confidence: 84%
See 1 more Smart Citation
“…In fact, the significant roles of development zones in promoting agglomeration of high-tech firms and industries has been confirmed in many empirical studies (Li & Zhu, 2017;Zhang, Huang, Sun, & Wang, 2013). In fact, the significant roles of development zones in promoting agglomeration of high-tech firms and industries has been confirmed in many empirical studies (Li & Zhu, 2017;Zhang, Huang, Sun, & Wang, 2013).…”
Section: Development Zones In China's Suburban Areasmentioning
confidence: 84%
“…As a major contributor to the suburbanization processes of Chinese cities, development zones are not only containers of manufacturing firms and related service companies but can also be incubators of new inventions and knowledge. In fact, the significant roles of development zones in promoting agglomeration of high-tech firms and industries has been confirmed in many empirical studies (Li & Zhu, 2017;Zhang, Huang, Sun, & Wang, 2013). In addition to the fact that development zones are usually located in the suburbs, there are at least two other factors that can facilitate the processes of knowledge generation and transfer in development zones.…”
Section: Development Zones In China's Suburban Areasmentioning
confidence: 92%
“…A study by Shima showed that regional compactness has a significant positive impact on innovative firms and regional innovation capacity [42,43]. Li found that accessibility can significantly affect the location choice for high-tech firms [29]. The research by Bettencourt demonstrated a super-linear relationship between the number of patent applications and the city size [44].…”
Section: Introductionmentioning
confidence: 99%
“…However, in studies on the location choice and the agglomeration of innovation, built environment was often conceptualized as part of the location factors. For example, the overall impact factor framework included the infrastructure [22], accessibility [29], and technology support levels [20]. Such an approach fails to provide a systematic analysis of the built environment.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the primary existing literature into account, Autant‐Bernard () investigated the location of research and development (R&D) activities in France; Arauzo‐Carod and Manjón‐Antolín () and Alamá‐Sabater et al . () of manufacturing establishments and firm birth, respectively, in Spain; and Li and Zhu () of R&D in Nanjing, China. In Japan, as far as we know, only Nguyen et al .…”
Section: Introductionmentioning
confidence: 99%